Optimation of meniran (Phyllanthus niruri L.) leaf extract using natural deep eutectic solvent basis choline chloride-glycol on antioxidant - Marybet Tri Retno Handayani; Yulianita Yulianita; Bina Lohitasari; Rieke Fitria P (JURNAL ILMU KEFARMASIAN INDONESIA, 2024)
Phyllanthus niruri L. has many benefits because it is known that meniran leaves contain secondary metabolites in the form of alkaloids, flavonoids, tannins, saponins and phenolics. The content of phenol compounds which are constituent compounds for antioxidant activity. This research was conducted to determine the combination of Natural Deep Eutectic Solvents (NADES) which can produce extracts with strong antioxidant activity. The preliminary stage determines the best combination of NADES with choline chloride as the Hydrogen Bond Acceptor and the type of sugar as the Hydrogen Bond Donor. The NADES screening obtained the best combination of choline chloride: glycerol, then the optimization stage was carried out using the RSM method with a Central Composite Design. Three variables used were temperature (25°, 40°, 60°C), time (10, 30, 60 minutes) and the ratio of NADES usage (50%, 70% and 90%). Antioxidant activity was determined with the value of in Meniran extract with positive control of vitamin C. The best NADES combination was choline chloride-glycerol (1:1) with an value of 18.039 ppm. Optimization with variations in temperature time and ratio variables obtained optimal conditions at temperature of 60°C with an extraction time of 44 minutes and ratio of 90% NADES obtained values IC50 values of 8.040 ppm and positive control of vitamin C obtained values IC50 values of 4.307 ppm. The best results for antioxidant activity are at a temperature of 60°C gives an value of 8.050 ppm was obtained and the average is 8.075 ppm.